AI insights : ethics audit and transformative power for entrepreneurs - Dawood, Hussein A. (Ethics in practice., 2025)
AI Insights: Ethics Audit and Transformative Power for Entrepreneurs offers a critical and timely exploration of how artificial intelligence is reshaping the entrepreneurial landscape. In this insightful work, Hussein Dawood delves into the ethical complexities surrounding AI adoption, particularly in small and medium-sized enterprises. Drawing on real-world case studies and rigorous academic research, the book provides entrepreneurs with actionable strategies to navigate challenges such as algorithmic bias, data privacy, security, and the tension between AI autonomy and human accountability. This book stands out by combining ethical audits with a transformative approach to innovation, empowering business leaders to harness AI responsibly. Entrepreneurs will find practical frameworks for ensuring AI integration aligns with both ethical standards and long-term business success. From ethical audits to practical implementation guides, AI Insights equips readers with the tools to foster sustainable growth while maintaining accountability and transparency in the age of AI. Whether you are a seasoned entrepreneur or just starting your journey, this book offers the insights needed to leverage AI for transformative power while ensuring ethical integrity remains at the core of innovation. It's not just a guide - it's a roadmap for the future of entrepreneurship in the AI era.